Unlocking Early Detection: The Role of DNA Methylation Biomarkers in Colorectal Cancer Tumorigenesis – A Systematic Review - Mohd Shukri, Nurul Izzati; Kaderi, Mohd Arifin; Alhabbal, Adel; Zainuddin, Norafiza (International Journal of Allied Health Sciences, 2024)
Keywords: colorectal cancer; DNA methylation; biomarkers; early detection Background: DNA methylation is an epigenetic mechanism that holds promise for improving disease detection, particularly in the early stages of neoplastic transformation. Although colonoscopy is currently the most effective method for detecting colorectal cancer (CRC) due to its high sensitivity, patient compliance is often hindered by its invasive nature, high cost, and inconvenient preparation process. This systematic review aims to systematically identify DNA methylation-based biomarkers used in early-stage CRC detection and to systematically compile evidence on the roles of DNA methylation-based biomarkers in CRC tumorigenesis. Methods: Data were collected via electronic searches for relevant citations from January 2018 to December 2023 in PubMed, Scopus, and Cochrane Library, using relevant and specific keywords for the search strategy. The selection of relevant articles is associated with the inclusion and exclusion criteria. The quality of the articles was assessed using the Crowe Critical Appraisal Tool (CCAT). Results: From an initial pool of 121 articles, 14 articles were selected based on the inclusion criteria and PRISMA guidelines. Conclusion: This systematic review successfully identified relevant DNA methylation-based biomarkers that have potential in early-stage CRC detection which are SDC2, KCNQ5, C9orf50, CLIP4, a combination of SEPT9 and SDC2, and a combination of GALNT9 and UPF3A. These biomarkers have been shown to have high accuracy and can be identified in a non-invasive approach such as stool and blood, demonstrating their potential as an effective tool for early CRC detection. Additionally, DNA methylation biomarkers were shown to be involved in key processes of CRC tumorigenesis, including cell proliferation, migration, transformation, metastasis, and angiogenesis.